Representativeness and inclusivity in pharmacological and nutraceutical interventions in youth mental health disorders: a systematic review and meta-analysis - Claudia Aymerich; Javier Torres-Cortés; Antonio Melillo; Borja Pedruzo; Ana Catalan; Olatz Ibarretxe; Chiara Nosarti; Katya Rubia; Celso Arango; Philip Shaw; Cornelius Ani; Hannah Chu-Han Huang; et al. (Nature Mental Health, 2026)
Abstract Randomized controlled trials (RCTs) guide treatment decisions in youth with mental health disorders, yet concerns remain about their generalizability. Here we conducted a Preferred Reporting Items for Systematic Reviews and Meta-Analyses-compliant systematic review and meta-analysis (CRD42024629137) to assess the inclusivity and representativeness of RCTs on pharmacological and nutraceutical interventions in children and adolescents with Diagnostic and Statistical Manual of Mental Disorders and/or International Classification of Diseases-defined mental disorders. Random-effects meta-analyses were conducted by disorder, and temporal trends were assessed. Primary outcomes were the representativeness of RCTs with respect to sex (pooled proportion of female participants) and race/ethnicity (distribution of racial and ethnic groups); secondary outcomes included the exclusion of key clinical populations (for example, autistic individuals, those with intellectual disability and those with suicide risk). A total of 397 RCTs (46,989 participants; mean age 10.2 ± 3.1 years) were included, mostly targeting attention deficit hyperactivity disorder (34.5%) or autism spectrum disorder (29.7%). Female participants represented 28.3%. Only 53.7% of RCTs reported racial data; 75.0% were white, 10.1% Black, 6.2% Hispanic and 2.0% Asian. Autistic individuals and those with learning disabilities were excluded in 56.5% and 44.3% of trials, respectively; 76.0% of depression RCTs excluded participants at suicide risk. There is a persistent mismatch between the youth most affected by mental health disorders and those included in RCTs. Some vulnerable populations including people of colour, women and special populations seem to be under-represented, requiring more inclusive practice to support equitable and effective care.